The scientific bases of human anatomy - Oxnard, Charles E., 1933- (Hoboken, New Jersey : Wiley-Blackwell, 2015)
As medical schools struggle to fit ever more material into a fixed amount of time, students need to approach the study of anatomy through a succinct, integrative overview. Rather than setting forth an overwhelming list of facts to be memorized, this book engages readers with a fascinating account of the connections between human anatomy and a wide array of scientific disciplines, weaving in the latest advances in developmental and evolutionary biology, comparative morphology, and biological engineering. 'Logically organized around a few key concepts, The Scientific Bases of Human Anatomy presents them in clear, memorable prose, concise tabular material, and a host of striking photographs and original diagrams.
A new system of human anatomy -- A bird's-eye view of the human body -- The naming of the parts, some wrinkles -- Building the human trunk -- Building human limbs -- Understanding the human head -- Building the human brain -- Postlude : possible human futures.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Human anatomy; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Human anatomy; Electronic books; Electronic books